Physical properties of ZnSe and CdSe semiconductor nanoparticles synthesized by thermal treatment and gamma irradiation routes - Salem, Aeshah Nizar (2016)
Several methods have been utilized previously to synthesize metal chalcogenide nanoparticles with enhanced chemical and physical properties. However, most of these methods have used a complicated procedure, longer reaction times, and employed toxic reagents of expensive materials. Current study employed two physical methods, the thermal treatment to synthesis pure ZnSe and CdSe semiconductor nanoparticles and their (Cd0.5Zn0.5)Se nanocomposite under a constant N2 gas flow. Gamma radiation method was used to prepare pure ZnSe and CdSe semiconductor nanoparticles. For the first method, an aqueous solutions of metal nitrate at different concentrations were mixed with 2 g of PVP, ethylenediamine(en) as a solvent of Se and deionized water as a solvent were prepared at calcination temperatures of 450-700°C. The samples were characterized by TGA, FTIR, EDX, XRD, TEM, and UV-Vis. FTIR analysis results confirmed the removal of organic matters and the presence of semiconductor nanoparticles at calcination temperatures 450-700°C. The elemental composition of the samples obtained by EDX spectroscopy has further evidence that the formation of ZnSe and CdSe nanoparticles and their nanocomposites. It was found that the phase formations of ZnSe and CdSe nanoparticles were cubic and hexagonal face-centered, respectively. The TEM images confirmed the increment of particle size from 12 to 26 nm for ZnSe and from 6 to 37 nm for CdSe and as well as from 12 to 24 nm for (Cd0.5Zn0.5)Se nanocomposites due to elevated calcination temperature and material concentration. The particle size of nanocrystals was also determined from XRD spectra. The estimated average sizes in the range 10.5-24 nm for ZnSe, 6-33 nm for CdSe nanoparticles and 10.5-25 nm for (Cd0.5Zn0.5)Se nanocomposites. While the optical properties were measured using UV-Vis spectrometer and the band gap ranged (3.956-4.158), (2.31-3.69) and (2.24-3.71) eV for ZnSe, CdSe and (Cd0.5Zn0.5)Se nanostructures, respectively. ZnSe and CdSe semiconductor nanoparticles were also synthesized using a single-step radiolytic approach in aqueous solution containing metal sulfite were mixed with 2 g of PVP, ethylenediamine(en), deionized water, and IPA alcohol under irradiation with Co-60 gamma rays at dose of 120 kGy. The hydrate electrons created in water are responsible for the formation of CdSe and ZnSe nanoparticles. The final samples were characterized by EDX, XRD, TEM, and UV-Vis. The X-ray powder diffraction patterns reveal successful hexagonal crystal structure for both CdSe and ZnSe nanoparticles, with the average crystallite sizes of 16.3 and 10.7 nm, respectively. The EDX was used to confirm the stoichiometric elemental composition of Zn, Cd and Se in the samples. The TEM micrograph shows that CdSe and ZnSe nanoparticles are spherical in shape, with an average diameter of 17.3 and 11.2 nm, respectively. The optical band gaps determined from UV-Visible absorption spectra are between 2.87 and 3.58 eV for the CdSe and ZnSe nanoparticles, respectively.